Field guide to the ICS clones of Trinidad - Johnson, Elizabeth (2004)
This Field Guide to the ICS Clones of Trinidad will be the first of a series dedicated to concisely presenting all available knowledge on cacao populations and collections. This guide presents detailed information on pod morphological descriptors, methods used to image pods, SSR genotyping and quantitative data. Additional information is available on pod morphologic al descriptors, quantitative data generation.